Genetic variability studies in F3 generation of mundu chilli (Capsicum annuum L.) for growth, yield and quality - Gadha Sreekumar1*, G. J. Janavi2, K. Nageswari1, K. Venkatesan3, C. Muthiah4 and M. Madhan Mohan5 (Electronic Journal of Plant Breeding, 2023)
A study was conducted on 16 growth, yield and quality characteristics in the F3 population derived from the Mundu Chilli cross PKM CA 32 x PKM CA 20, encompassing genetic variability, heritability and genetic advancement. The progenies in the population were assessed using 16 parameters, encompassing on aspects such as growth, yield, and quality. The success of varietal improvement relies on the genetic variability in existing material. Assessing the nature and extent of variability in the germplasm stock is a crucial step for effective breeding methods. The study found significant levels of genetic diversity in every trait examined in each progenies in the cross. High GCV and PCV were observed for yield of fruits per plant (both dry and ripe), oleoresin and capsaicin, suggesting greater variability and high heritability estimates with considerable genetic advancement as percentage of mean indicating these traits could increase the fruit yield and quality.